Global prevalence of human pegivirus‐1 in healthy volunteer blood donors: a systematic review and meta‐analysis. Issue 3 (16th December 2019) - Yang, Na; Dai, Run; Zhang, Xiaojun
Abstract: Background and objectives: The local prevalence of HPgV‐1 has been reported from different countries worldwide, but the global prevalence of HPgV‐1 remains unknown. The aim of this systematic review and meta‐analysis was to gather data from the literature to estimate the prevalence of HPgV‐1 in healthy volunteer blood donors in the world. Materials and methods: We searched PubMed, EMBASE, Scopus and Google Scholar databases for records up to January 2019 and included studies reporting HPgV‐1 virus prevalence amongst healthy volunteer blood donors based on the detection of HPgV‐1 RNA. Results: In all, we included 79 studies for the systematic review and 63 for the meta‐analysis. Based on the random effect meta‐analysis of 35 468 volunteer blood donors, we found the global prevalence of HPgV‐1 to be 3·1% (95% CI, 2·4–4·1). The pooled prevalences of HPgV‐1 were 1·7% (95% CI, 1·1–2·6) in North America, 9·1% (95% CI, 6·4–12·7) in South America, 2·3% (95% CI, 2%, 2·8) in Europe and 2·4% (95% CI, 1·4–4) in Asia. Subgroup analyses based on age, gender or risk factors were not possible. Conclusion: Approximately 3 in 100 blood donations worldwide are positive for HPgV‐1 increasing the risk of infection from transfusion of their components to subsequent recipients. Further research on virus pathogenicity is required before recommending routine screening of HPgV‐1 for healthy volunteer blood donors.